Previous competences of information technology governance for the board of directors in Indonesia - SOMJAI, S.; RUNGSAWANPHO, D. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACTThis study focuses on the requirement of having a mechanism with respect to IT systems, highlighting any visible conflict between the organization and the IT governance structure. The aim of this study is to create an IT competence prototype that will facilitate attaining desired IT governance. Implications of this research are that the specific prototype developed can be used to gauge the IT competency in other domains. Moreover, the results and findings of this study can also be used as a starting point for future researches. RESUMENEste estudio se centra en el requisito de tener un mecanismo con respecto a los sistemas de IT que resalte cualquier conflicto visible entre la organización y la estructura de gobierno de IT. El objetivo de este estudio es crear un prototipo de competencia de IT que facilitará el logro del gobierno de IT deseado. Las implicaciones de esta investigación son que el prototipo específico desarrollado puede usarse para medir la competencia de IT en otros dominios. Además, los resultados y hallazgos de este estudio también se pueden utilizar como punto de partida para futuras investigaciones.